Analisis Koneksi Matematis Siswa SD Inpres Pa’bangiang dalam Mengaitkan Konsep Materi Pecahan dalam Kehidupan Sehari-Hari - Nur Fadillah Amir; Syarifuddin Syarifuddin (Lembaga Yasin AlSys, 2026)
Mathematical connection skills are an important aspect of elementary school mathematics learning because they help students relate mathematical concepts to everyday experiences and situations. However, students’ ability to connect fraction material with real-life contexts still needs to be examined in greater depth, particularly among Grade V students at SD Inpres Pa’Bangiang, Gowa Regency. This study aims to analyze students’ mathematical connection skills in relating the concept of fractions to everyday life. This study used a descriptive qualitative approach involving 30 Grade V students as research subjects. Data were collected through tests, interviews, and documentation, with instruments in the form of essay questions on fraction material containing indicators of mathematical connection skills. Data were analyzed through the stages of data reduction, data display, and conclusion drawing. The results showed that students’ mathematical connection skills were in the moderate category. Some students were able to connect the concept of fractions with everyday activities, such as sharing food, measuring cooking ingredients, and buying and selling transactions. However, difficulties were still found in relating the concept of fractions to other mathematical representations and applying it to more complex contextual situations. Factors influencing this condition included a lack of contextual learning, low understanding of basic fraction concepts, and limited use of learning media. These findings indicate the importance of implementing more innovative, contextual, and real-experience-based learning strategies to improve elementary school students’ mathematical connection skills. The implications of this study provide practical contributions for teachers in designing more meaningful fraction learning and strengthening students’ understanding of the relationship between mathematical concepts and everyday life.